IMPLEMENTASI RESTFUL WEB SERVICE PADA APLIKASI PEMESANAN SUKU CADANG BERBASIS WEB DI AHASS MUNJUL MOTOR - R.A. S Zarkasih; Dikki Febri Willianto; Soecipto Soecipto (Jurnal Computech & Bisnis (e-Journal), 2021)
AHASS Munjul Motor is an official Honda bicycle workshop which is engaged in the maintenance of Honda motorcycles and serves the purchase of Honda motorcycle parts. AHASS Munjul Motor provides a variety of genuine Honda motorcycle parts. In ordering parts to suppliers for ordering purposes, AHASS Munjul Motor still uses the manual method. This requires a long time so that the work becomes less effective. Often asking for errors in ordering parts fo suppliers. Restful web services are the standard for conducting data between applications or systems. This research implemented a quiet web service to integrate the AHASS munjul motor systems with the system supplier. Providing, providing AHASS munjul motorcycles in ordering spare parts and maing it easier for suppliers to accept spare parts orders.  Keywords: Restful Web Service, Web Based Application, Spare Parts.DOI : http://doi.org/10.5281/zenodo.4958400